Assessing the Need for Disaster Mitigation-Based Textbooks in Indonesian Language Learning: A Study of Junior High Schools in Palu City - Ulfah Ulfah; Juniati Juniati; Hasnur Ruslan; Nur Halifah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Disaster-prone areas like Palu City require educational materials integrating disaster mitigation into the curriculum. This study investigates the need for disaster mitigation-based textbooks in Indonesian language learning at junior high schools, emphasizing students' and teachers' expectations for effective learning resources. This research follows the Research and Development (RD) approach using the ADDIE model, focusing on the analysis stage. A questionnaire was distributed to 200 students and 20 teachers in junior high schools in Palu City to assess their needs and preferences regarding textbooks. Findings indicate that printed textbooks remain the primary learning resource, with 70% of students and 90% of teachers using them. However, disaster mitigation content is significantly lacking, as 30% of students and 50% of teachers do not have textbooks covering this topic. The study highlights the demand for contextualized disaster mitigation materials, with 90% of students and 85% of teachers preferring visual elements to enhance comprehension. Additionally, 75% of students and 80% of teachers find quizzes engaging, while 95% of students and 75% of teachers value interesting facts. Language clarity is also crucial, with 90% of students and 80% of teachers favouring easy-to-understand language. To improve learning effectiveness, disaster mitigation-based textbooks should incorporate relevant content, engaging visual aids, and accessible language. This study underscores the importance of developing disaster mitigation-integrated textbooks to enhance both language learning and disaster preparedness. Future research should explore localized content integration and interactive teaching strategies for disaster-prone areas.